2004
DOI: 10.1038/sj.jhh.1001772
|View full text |Cite
|
Sign up to set email alerts
|

Comparing office-based and ambulatory blood pressure monitoring in clinical trials

Abstract: Ambulatory blood pressure monitoring (ABPM) is commonly used in clinical trials. Yet, its ability to detect blood pressure (BP) change in comparison to multiple officebased measurements has received limited attention. We recorded ambulatory and five daily pairs of random zero (RZ) BPs pre-and post-intervention on 321 adult participants in the multicentre Dietary Approaches to Stop Hypertension trial. Treatment effect estimates measured by ambulatory monitoring were similar to those measured by RZ and did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Indeed, the increasingly valuable role of ambulatory blood pressure monitoring in risk assessment, prognostic and therapeutic guidance is well recognized. [15][16][17][18] This same principle is surprisingly not been tested in biomarkers and is long overdue. Simply, the temporal pattern of repeated measures over a set time interval might define disease progression, stability or pending instability, for the individual regardless of symptomatic state (or potentially despite it!).…”
Section: Could Repeated Measures Of Biomarkers or The Variance Thereomentioning
confidence: 99%
“…Indeed, the increasingly valuable role of ambulatory blood pressure monitoring in risk assessment, prognostic and therapeutic guidance is well recognized. [15][16][17][18] This same principle is surprisingly not been tested in biomarkers and is long overdue. Simply, the temporal pattern of repeated measures over a set time interval might define disease progression, stability or pending instability, for the individual regardless of symptomatic state (or potentially despite it!).…”
Section: Could Repeated Measures Of Biomarkers or The Variance Thereomentioning
confidence: 99%
“…ABP treatment differences usually agree well with the result from clinic measures, and treatment was effective when measured by both methods. [26][27][28] The difference between the groups was 8/4 mm Hg for night-time ABP and even higher in the 52 participants with ABP measurements at baseline and during follow-up (online-only Data Supplement). Over 65 years of age, night-time ABP is a better predictor of cardiovascular events than the CBP and other measures of ABP.…”
Section: -25mentioning
confidence: 99%
“…5 As 24-h ambulatory BP monitoring (ABPM) can now be easily performed with reliable monitoring devices, a number of studies have shown the inadequacy of evaluating BP control from clinical measurements alone. 6,7 Recent studies have indicated that home BP (HBP) measured in the morning has a stronger predictive power for mortality than does office BP measurement. 8,9 These reports suggest the importance of monitoring morning HBP, in addition to office BP, to evaluate BP control and to adjust antihypertensive therapy.…”
Section: Introductionmentioning
confidence: 99%